2001
DOI: 10.1038/sj.onc.1204501
|View full text |Cite
|
Sign up to set email alerts
|

A splice variant of Skp2 is retained in the cytoplasm and fails to direct cyclin D1 ubiquitination in the uterine cancer cell line SK-UT

Abstract: Cyclin D1 is an important regulator of the transition from G1 into S phase of the cell cycle. The level to which cyclin D1 accumulates is tightly regulated. One mechanism contributing to the control of cyclin D1 levels is the regulation of its ubiquitination. SK-UT-1B cells are de®cient in the degradation of D-type cyclins. We show here that p27, a substrate of the SCF Skp2 ubiquitin ligase complex, is coordinately stabilized in SK-UT-1B cells. Further, we show that expression of Skp2 in SK-UT-1B cells rescues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 36 publications
2
56
1
Order By: Relevance
“…SCF complexes containing the F-box protein Skp2 promote the ubiquitylation and degradation of cyclin D1 (39,40). Thus defects in the Ubmediated proteolysis of cyclin D1 by proteins such as Skp2 lead to the stabilization of cyclin D1 in several cancer cell lines (40,41). Therefore, aspartate 199-dependent stabilization of cyclin D1 mediated by ICP0 (16) may result from the degradation of cdc34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCF complexes containing the F-box protein Skp2 promote the ubiquitylation and degradation of cyclin D1 (39,40). Thus defects in the Ubmediated proteolysis of cyclin D1 by proteins such as Skp2 lead to the stabilization of cyclin D1 in several cancer cell lines (40,41). Therefore, aspartate 199-dependent stabilization of cyclin D1 mediated by ICP0 (16) may result from the degradation of cdc34.…”
Section: Discussionmentioning
confidence: 99%
“…Cdc34 is the major E2 that interacts with the Skp1-cdc53-F-box (SCF) E3 complex (14). SCF complexes containing the F-box protein Skp2 promote the ubiquitylation and degradation of cyclin D1 (39,40). Thus defects in the Ubmediated proteolysis of cyclin D1 by proteins such as Skp2 lead to the stabilization of cyclin D1 in several cancer cell lines (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12]. This function has been proposed to be mediated by the catalytic subunit CSN5 but requires the assembly of the entire CSN holocomplex (10)(11)(12)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The deneddylation of Cullins is required for Cullin-mediated degradation of E3 substrates.…”
Section: Cop9 Signalosomementioning
confidence: 99%
“…[44][45][46][47] as well as several cyclins (cyclin D1, cyclin E, and cyclin B1; refs. 17,20,24,28). Theoretically, inhibition of Cullin activity would promote accumulation of the cyclin-dependent kinase inhibitors, restoring control to cell cycle and inhibiting cell proliferation.…”
Section: Cell Cyclementioning
confidence: 99%
“…Marti et al (1999) reported that the transcription factor E2F1 is able to bind Skp2 and Cul1, and that mutations in the E2F1 N-terminal region that abolish binding to Skp2 decrease E2F1 ubiquitinylation and lead to its stabilization. Moreover, Skp2 seems to play a role in the ubiquitinylation and degradation of Cyclin D1 and Cyclin E. Cyclin D1, which is overexpressed in several human tumors, is ubiquitinylated and degraded by the proteasome, and some lines of evidence indicate that Skp2 might be implicated, at least in part, in this process (Yu et al, 1998b;Ganiatsas et al, 2001). Finally, Nakayama et al (2000) found that Skp2 can bind to the CDK-unbound, inactive form of Cyclin E and mediate its ubiquitinylation.…”
Section: Scf Skp2mentioning
confidence: 99%